THE EFFECT OF LOCAL REVENUE AND REVENUE SHARING ON ECONOMIC GROWTH IN EAST JAVA( Case Study of District/City in East Java Province Period of 2011-2015 ) - Ingtyas, Ajeng Jasita (Jurnal Ilmiah Mahasiswa FEB, 2017)
The purpose of this research is to know and analyze whether the General Allocation Fund, Special Allocation Fund, DBH and Local Revenue effect on Slowing Economy districts / cities in East Java. The method used in this research is quantitative method with regression testing panel to test the Redundant Fixed Effect Test (Test Chow), Correlated Random Effects - Test and Lagrange MutlipierHausman Test. variables used in this study is the General Allocation Fund, Special Allocation Fund, Sharing Revenue and Regional Income as independent variables and variable Economic Growth as the dependent variable.Total population of this study were 38 districts / municipalities period 2011-2015. The results of this study prove that in partial General Allocation Fund and Special Allocation Funds have a significant effect to Economic Growth in the districts / cities in East Java, while the income of DBH and original local no significant effect on economic growth in the districts / cities in East Java. Thus, to the districts / cities in East Java DAU and DAK as a means of equalization Fiscal result of fiscal gap, which needs DAU and DAK an area determined by the needs of local and regional potentials that determine the fulfillment of the composition Economic Growth of districts / cities in East Java.Keywords: Local Revenue, Revenue Sharing, Generally Allocation Fund, Specially Allocation Fund and Economic Growth